Formulation and Evaluation of Tetanus Leaf (Leea aequata L.) Ethanol Extract on Tablet Preparation using Wet Granulation Method - Ningsih, Wulan Seppia; Bangar, Roy Indrianto; Kaban, Vera Estefania; Harahap, Daimah Wirdatus Sanaun (CV. Nusantara Scientific Medical, 2025)
Degenerative diseases are currently widely suffered, especially in Indonesian society, as many as 30% of the population is detected with degenerative diseases. One alternative treatment that is widely consumed by Indonesian society is herbal or traditional medicine, one of the plants that is widely consumed by society, especially in Indonesia, namely Tetanus Leea Aequata L leaves. These leaves are often found, especially in the Karo area. The purpose of this study was to use ethanol extract of tetanus Leea Aequata leaves as tablets using the wet granulation method. The content contained in the leaves, such as Flavonoids, can be used as an alternative medicine to treat degenerative diseases by using a comparison of muchilago amyli used as a binder, namely f1 20%, f2 10% and F3 5% based on this study, a formula was obtained that can be used to make tablets, namely formula 1 20% muchilago amyli